Penerapan Whistleblowing System dalam Pengungkapan Fraud - Aristianingrum, Dwi Prisma; Zaidan, Naufal Ali; Putri, Negina Kencono; -, Agus Sunarmo (Jurnal Riset Akuntansi Soedirman, 2025)
This study aims to determine whether the implementation of the whistleblowing system affects fraud disclosure in banking sector companies listed on the Indonesia Stock Exchange in 2019-2022. The population in the study was 248 companies. The sampling technique used purposive sampling so that the sample of this study was 96 companies. This research method uses quantitative methods. The proxy for the fraud disclosure variable uses fraud cases disclosed in the company's annual report, while for the whistleblowing system variable uses the formula for the report component indicators carried out in the KNKG. The results of this study indicate that the implementation of the whistleblowing system has a positive but insignificant effect on fraud disclosure.